2009
DOI: 10.1007/s11458-009-0025-8
|View full text |Cite
|
Sign up to set email alerts
|

Flowerlike MoS2 nanoparticles: solvothermal synthesis and characterization

Abstract: Flowerlike MoS 2 nanoparticles have been successfully synthesized through a mild solvothermal reaction with the aid of ethanol aqueous solution, and the samples have been characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), and low temperature nitrogen adsorption-desorption. The nanometer flower MoS 2 is composed of ultrathin nanosheets of approximately 10 nanometers in thickness. The influence of the reaction temperature and the reaction time on the formation of the flowerlike MoS 2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Materials Advances 500 1C. 62 The authors observed that a lower temperature and reaction time leads to formation of MoO 2 impurities. Several researchers have also reported synthesis of nano-MoSe 2 by the solvothermal method using an autoclave.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials Advances 500 1C. 62 The authors observed that a lower temperature and reaction time leads to formation of MoO 2 impurities. Several researchers have also reported synthesis of nano-MoSe 2 by the solvothermal method using an autoclave.…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, flower like nanoparticles composed of ultrathin nanosheets of MoS 2 have been reported by use of the sodium molybdate, thiourea and hydroxylamine hydrochloride mixture (1 : 2 : 2 molar ratio) in an autoclave heated for 24 h at 190 °C, followed by annealing for 5 h at 500 °C. 62 The authors observed that a lower temperature and reaction time leads to formation of MoO 2 impurities.…”
Section: Synthesismentioning
confidence: 99%
“…MoS 2 nanostructures of various shapes such as 2D sheets [7], nanoparticles (NP) [8], nanospheres (NS) [9], nanorods [10], nanoflowers [11], and quantum dots [12] are gaining attention over the past decade and are prepared by methods such as exfoliation [13], chemical vapor deposition(CVD) [14], hydrothermal/solvothermal methods [15], gas-phase synthesis [16], sol-gel methods [17] etc. The synthesis of MoS 2 NS is generally carried out using hydro/solvothermal methods at high temperatures using various precursors in the presence of a reducing agent, for e.g.…”
Section: Introductionmentioning
confidence: 99%